Money Laundering As A Transnational Crime Problems And The Ideas Of Legal Policy Reformation In Indonesia - Japriyanto Japriyanto; Desia Rakhma Banjarani; Risa Mahdewi (Faculty of Law, Universitas Lampung, 2022)
Various countries today are threatened by money laundering as a transnational crime known as borderless crime. This is because the impact of money laundering is not ordinary. The crime of money laundering has a considerable impact disrupting the stability of the economy and social life and even damaging the world economic order. However, various legal problems in dealing with money laundering often occur in Indonesia. With these various problems, it shows that Indonesia needs a legal reformulation related to money laundering as classified as a transnational crime. Based on this background, this research will discuss the problems of how money laundering can be classified as a transnational crime, the problems with its law enforcement, and the legal policy of money laundering as a transnational crime reformulation in Indonesia. This study uses a descriptive normative research method with a qualitative approach. The results show that the idea of reformulation in law enforcement of money laundering as a transnational crime in Indonesia is through the reconstruction of Mutual Legal Assistance or MLA between the Indonesian government and various countries in the world and the application of other international instruments, such as extradition and confiscation. Then regarding the problem of money laundering in law enforcement, it is necessary to reformulate the authority of the Corruption Eradication Commission or KPK to prosecute money laundering crimes originating from the criminal act of corruption because the Anti-Money Laundering Law has not yet clearly regulated the law enforcers who are authorized to carry out prosecutions for the Crime of Money Laundering. So to overcome this law enforcement problem, it is necessary to reform the money laundering law.